Brain amyloid in preclinical Alzheimer's disease is associated with increased driving risk. Issue 1 (29th November 2016) - Ott, Brian R.; Jones, Richard N.; Noto, Richard B.; Yoo, Don C.; Snyder, Peter J.; Bernier, Justine N.; Carr, David B.; Roe, Catherine M.
Abstract: Introduction: Postmortem studies suggest that fibrillar brain amyloid places people at higher risk for hazardous driving in the preclinical stage of Alzheimer's disease (AD). Methods: We administered driving questionnaires to 104 older drivers (19 AD, 24 mild cognitive impairment, and 61 cognitive normal) who had a recent 18 F‐florbetapir positron emission tomography scan. We examined associations of amyloid standardized uptake value ratios with driving behaviors: traffic violations or accidents in the past 3 years. Results: The frequency of violations or accidents was curvilinear with respect to standardized uptake value ratios, peaking around a value of 1.1 (model r 2  = 0.10, P  = .002); moreover, this relationship was evident for the cognitively normal participants. Discussion: We found that driving risk is strongly related to accumulating amyloid on positron emission tomography, and that this trend is evident in the preclinical stage of AD. Brain amyloid burden may in part explain the increased crash risk reported in older adults.